2021
DOI: 10.17159/2519-0105/2021/v76no7a4
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic status and treatment need of 13 to 15 year-old children in Kwa-Zulu Natal South Africa: An epidemiology study using the Dental Aesthetic Index (DAI)

Abstract: The prevalence of malocclusion among school going children in KwaZulu-Natal remains poorly defined despite the known physiological and psychological impact of this dental occurrence. The aim and objectives of this study was to determine the prevalence of malocclusion and possible treatment need in 13-15 year-old school going children in Durban, Kwa-Zulu Natal. This was a descriptive, cross-sectional epidemiological study conducted on 270 school-going children aged 13 to 15 years, in the Umlazi and Pinetown sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This age range allows for early detection of malocclusion and subsequently early intervention which permits better resource allocation. [24] Regarding the AC of IOTN, the results of the present study displayed that 75.8% of the examined population showed no or slight need for orthodontic treatment, 7% demonstrated moderate or borderline need and 17.2% revealed definite orthodontic treatment need. Concerning the DHC of IOTN, 28.5% of the examined children showed no need for orthodontic treatment, 36.9% displayed mild /little need, 7.3% exhibited moderate/ borderline need, 25.8% demonstrated severe need and 1.5% manifested an extreme need for orthodontic treatment.…”
Section: Discussionmentioning
confidence: 49%
“…This age range allows for early detection of malocclusion and subsequently early intervention which permits better resource allocation. [24] Regarding the AC of IOTN, the results of the present study displayed that 75.8% of the examined population showed no or slight need for orthodontic treatment, 7% demonstrated moderate or borderline need and 17.2% revealed definite orthodontic treatment need. Concerning the DHC of IOTN, 28.5% of the examined children showed no need for orthodontic treatment, 36.9% displayed mild /little need, 7.3% exhibited moderate/ borderline need, 25.8% demonstrated severe need and 1.5% manifested an extreme need for orthodontic treatment.…”
Section: Discussionmentioning
confidence: 49%
“…[ 16 27 ] While the studies by Grewe and Hagan are older studies, more recent ones have focused on the prevalence rates of posterior crossbite without identifying the BRB. [ 19 28 29 ] In this study, the rarity of the BRB was inferred from the low values over the 3-year period, which were 0.5% in Benin City and 2.3% in Abuja, Nigeria. This disparity could be attributed to the larger sample size of the untreated orthodontic patients in one of the geo-political zones.…”
Section: Discussionmentioning
confidence: 86%
“…Most studies have identified only the presence of a posterior crossbite. Drummond[ 19 ] reported a prevalence of 10.4% in a South African population, whereas in an Indian population, a prevalence of 5.5% was reported by Nainani and Relan. [ 29 ] These studies,[ 19 28 29 ] however, had recorded posterior crossbites and not BRBs, which are more uncommon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations